1990
DOI: 10.1017/s0252921100005121
|View full text |Cite
|
Sign up to set email alerts
|

A Spiral-Like Disk of Ionized Gas in IC 1459: Signature of a Merging Collision?

Abstract: Abstract. We report the discovery of a large (15 kpc diameter) Ha+[NII] emission-line disk in the elliptical galaxy IC 1459, showing weak spiral structure. The line flux peaks strongly at the nucleus and is more concentrated than the stellar continuum. The major axis of the disk of ionized gas coincides with that of the stellar body of the galaxy. The mass of the ionized gas is estimated to be ~ 1 10 M Q , less than 1% of the total mass of gas present in IC 1459. The total gas mass of 4 10 M© has been estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
45
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 14 publications
10
45
0
Order By: Relevance
“…In addition to the dust located at its center, IC1459 has large strip of dust lining from the south-east to the north-west on its west side. Goudfrooij et al (1990) identified some potential spiral arms in Hα maps of IC1459 that extend about 40" away from its center. The location of the two largest Hα arms seems to coincide with the location of the structures present north of the galaxy center in the 160µm map, although the FIR structures do not resemble closely the shape of spiral arms.…”
Section: Ic1459 Analysismentioning
confidence: 99%
“…In addition to the dust located at its center, IC1459 has large strip of dust lining from the south-east to the north-west on its west side. Goudfrooij et al (1990) identified some potential spiral arms in Hα maps of IC1459 that extend about 40" away from its center. The location of the two largest Hα arms seems to coincide with the location of the structures present north of the galaxy center in the 160µm map, although the FIR structures do not resemble closely the shape of spiral arms.…”
Section: Ic1459 Analysismentioning
confidence: 99%
“…The diffuse X-ray emission has an ellipticity of about e $ 0:15, and the position angle twists from P:A: $ 135 for r < 50 00 to P:A: $ 110 at larger radii (Buote et al 2002). The stellar light has e ¼ 0:45 AE 0:05 and P:A: ¼ 142 AE 3 , and the distribution of globular clusters follows e ¼ 0:5 AE 0:1 and P:A: ¼ 147 AE 10 ( Kissler-Patig, Richtler, & Hilker 1996;Peletier et al 1990;Goudfrooij 1994). Figure 6a shows the angular distribution of X-ray sources.…”
Section: Spatial Distributionmentioning
confidence: 99%
“…The IC 1459 galaxy itself has a number of peculiar features, hinting at disturbances due to interactions and/or merging: twisted isophotes first noticed by Williams & Schwarzschild (1979) and Franx et al (1989), a fast counter-rotating stellar core (Franx & Illingworth 1988), faint stellar shells (Malin 1985) and a large H + N [iii] emission-line disc showing a weak spiral structure (Goudfrooij et al 1990). Furthermore, IC 1459 hosts a bright radio source, PKS 2254-367, characterised by two symmetric radio jets, whose activity may have been triggered by the same events that gave the galaxy its peculiar morphology and kinematics.…”
Section: The Ic 1459 Galaxy Groupmentioning
confidence: 99%